2019
DOI: 10.1186/s12993-019-0160-4
|View full text |Cite
|
Sign up to set email alerts
|

Neuroprotective effects of Withania somnifera in BPA induced-cognitive dysfunction and oxidative stress in mice

Abstract: Background Bisphenol A (BPA), a major endocrine disruptor and a xenobiotic compound is used abundantly in the production of polycarbonate plastics and epoxy resins. Human exposure to this compound is primarily via its leaching from the protective internal epoxy resin coatings of containers into the food and beverages. In addition, the plastics used in dental prostheses and sealants also contain considerable amount of BPA and have a high risk of human exposure. Since it is a well-known endocrine di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
28
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 75 publications
(29 citation statements)
references
References 62 publications
0
28
0
1
Order By: Relevance
“…In neurodegenerative disease, brain is especially vulnerable to oxidative damage, due to the imbalance between the generation of oxygen free radicals and antioxidant defense system (Birla et al, ; Gupta et al, ; Y. Singh et al, ). In this study, MDA level was elevated while a decrease in SOD, CAT and GSH level was observed in Aβ‐infused group which indicated oxidative damage in the brain.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In neurodegenerative disease, brain is especially vulnerable to oxidative damage, due to the imbalance between the generation of oxygen free radicals and antioxidant defense system (Birla et al, ; Gupta et al, ; Y. Singh et al, ). In this study, MDA level was elevated while a decrease in SOD, CAT and GSH level was observed in Aβ‐infused group which indicated oxidative damage in the brain.…”
Section: Discussionmentioning
confidence: 99%
“…In neurodegenerative disease, brain is especially vulnerable to oxidative damage, due to the imbalance between the generation of oxygen free radicals and antioxidant defense system (Birla et al, 2019;Gupta et al, 2012;Y. Singh et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Ashwagandha supplementation could be an effective alternative that can counter aging issues including sleep quality and mental alertness improvement. Earlier evidence suggests that Ashwagandha impacts positively on overall well-being including an antioxidant effect which is essential in age-related problems [23].…”
Section: Discussionmentioning
confidence: 99%
“…Scientists have been working on natural alternatives which provide e cient neuroprotection, subsequent impending basic pathological conditions [11]. The literature study revealed that several medicinal plants including Mucuna pruriens, Bacopa monnieri, Withania somnifera, Tinospora cordifolia (Tc) and their active constituents have neuroprotective effects against neuronal cell death in PD [12][13][14][15][16].…”
Section: Introductionmentioning
confidence: 99%